FAKTOR YANG BERHUBUNGAN DENGAN DISIPLIN PENGGUNAAN ALAT PELINDUNG DIRI PADA PENYAPU JALAN DI KOTA SEMARANG - Iqlima Intan Yulita; Baju Widjasena; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Labor in Indonesia mostly work on the informal sector. The informal sector has no clear employment contract as well as the assurance of the safety and health of less note. Each workforce has the right to obtain the protection of the safety and health of work. The use of the APD is the level of the hierarchy of control last but its application is highly recommended. The purpose of this research is to analyze the relationship of factors that affect the use of personal discipline. This research uses descriptive correlative with design research cross sectional study. The population of this research was a street sweeper in Semarang city as many as 148 people. The number of samples taken for as much as 60 respondents. Sampling techniques using incidental sampling. Instrument research using questionnaires. Statistical tests using the chi-square test with a confidence level of 95%. Test results indicate the value p-value <0,05 for variables of the knowledge, attitudes, education, availability of APD, co-workers. While in the variable age p-value 0.05. The results of the analysis showed the existence of a relationship between knowledge, attitude, education, availability of APD, a co-worker with a disciplined use of the APD. The results of the analysis of the variables of age showed no relationship with disciplined use of the APD. Then it can be inferred that there is a significant relationship between knowledge, attitude, education, availability of personal protection and the role of co-workers with the disciplined use of the APD.